Implementation of Government Affairs of Population Administration and Civil Registration which are the Authority of the Region - Richard Olbi; Fero Sanjaya; Herlita Eryke (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study examines the implementation of population administration and civil registration as a regional authority in Bengkulu Province, with a focus on the balance between regulations and field practices. The study aims to analyze the effectiveness of population administration implementation at the regional level, particularly in the context of electronic-based services and the Child Identity Card (KIA) policy, and to identify factors that hinder the achievement of effective and inclusive services. The study uses a normative legal research type with a qualitative approach, supported by a library study of laws and regulations, literature, and previous research results. Therefore, it does not use a population and statistical sample but rather a selection of case studies in Bengkulu Province as a limited empirical analysis. Data were collected through regulatory analysis and case study reviews, then analyzed interpretively and systematically to illustrate the relationship between norms and practices. The results show that although the regulatory framework and digital innovations such as the SLAWE application and the KIA program have been implemented, their implementation is still limited by limited human resources, technological infrastructure, and low literacy and community participation. The research conclusion emphasizes the need to strengthen the institutional capacity of the Civil Registration Office (Disdukcapil), improve facilities and infrastructure, and expand outreach and synergy between agencies so that civil registration services in the regions run effectively, transparently, and inclusively for all levels of society.